Knowledge, attitude, and husband's support as predictors of postpartum visit adherence: A cross-sectional study - Herien, Yelly; Muthmainnah; Qhalida, Melsa Hazharia (Pediomaternal Nursing Journal, 2025)
Introduction: Postpartum visits are crucial for postpartum mothers as they play a significant role in ensuring the health and well-being of both the mother and the newborn. Nevertheless, only few postpartum women have attended all of the required postpartum visits. This study aimed to determine the factors associated with postpartum visits in Seberang Padang Village, Padang, Indonesia. Methods: This study was a descriptive analytical study with a cross-sectional approach. The Total Sampling approach was used to collect data from 43 postpartum women with infants ages 6 to 8 weeks. A questionnaire about respondent characteristics, knowledge, attitude, spouse support, and postpartum visit was utilized to collect data. Chi-square was employed for bivariate analysis, and logistic regression was used for multivariate analysis. Results: Postpartum visits were associated with knowledge (P-value = .038), attitude (P-value = .001), and husband’s support (P-value = .006), according to bivariate analysis. Multivariate analysis revealed that attitude, with P-value = .021 and Exp (B) = 15.188, was the most significant variable linked to postpartum visits. Conclusion: To increase postpartum mothers' understanding of how to conduct postpartum visits, health professionals are anticipated to host communication, information, and education events. This practice is intended to enhance postpartum moms' knowledge, attitudes, and desire to have postpartum checkups. Keywords: attitude; husband’s support; knowledge; pospartum visit